A System Approach to Teaching the Accounting Process. - Mead, George C.; Singer, Frank A. (The Accounting Review, 1970)
The article presents an approach to teaching basic accounting concepts, a system approach involving programmed materials reinforced by frequent and immediate feedback to students on an individual progress basis. The approach offers worthwhile advantages not available through conventional approaches to basic concepts or through use of any one of the system's elements alone. The article gives a description of the main features of the instructional system, some observations on the system's contributions and results, discussion of some unsolved problems and a summary and some recommendations derived from the experience. There do appear to be substantial advantages from considering the impact of each element in the teaching-learning situation and further advantages from seeking a complimentary combination of these elements. All this confirms the advice of educational technologists. They would agree that all perceived advantages should not be expected from the adoption of any one system element-such as the instructional program, or testing, or the feedback arrangement. Only when the coordination of appropriate elements organizes reinforcement of behavior in a system directed at clearly perceived goals, should one hope for large gains.